Pengambangan Materi Ajar Teks Cerita Rakyat (Hikayat) Berbantuan Aplikasi Macromedia Flash Kelas X SMA - Rika Wahyuni Harahap; Syamsul Arif (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research aims to determine (1) The form of teaching materials in folklore texts (saga) assisted by the Class X Macromedia Flash application (2) The process of developing teaching materials in folklore texts (saga) assisted by the Class on folklore texts (saga) assisted by the Class X Macromedia Flash application (4) effectiveness of teaching materials on folklore texts (saga) assisted by the Class The trial was carried out in class X MIA at MAS Miftahul Falah Diski. The object of this research is folklore text teaching material assisted by the Macromedia Flash application. The results show 1) The validity of the teaching materials developed is included in the valid category with an average value of total material validity of 88.3% from material experts and 87.5% from media experts. 2) The effectiveness of classical completeness reached 86.4%, that is, it had met the completeness criteria, namely ≥ 85% of students reached the KKM. 3) Student responses show interest in learning with teaching materials developed with the help of Macromedia Flash on folklore (saga) text material seen from the average student response questionnaire score in product trials of 89.20% in the interesting category.